Genotoxicity In Chironomus Kiiensis (Chironomidae: Diptera) after Exposure To Polluted Sediments from Rivers of North Peninsular Malaysia: Implication For Ecotoxicological Monitoring - Salman A., Al-Shami; Che Salmah, Md Rawi; Siti Aziziah, Mohd Nor mohd Nor; Abu Hassan, Ahmad; Nur Adibah, Mohd Ishadi; Dieng, Hamady (Wiley Online Library, 2012)
Rapid industrialization and urbanization has led to increasing input of chemical contaminants into the aquatic environment of Malaysia. Despite the threat civilization poses to the biota, there are still very few relevant studies on ecotoxicological testing of river ecosystems. To overcome this knowledge gap,we examined lethal and genotoxic effects of sediments fromdifferent rivers of the northernMalaysia against Chironomus kiiensis, a group well represented in the aquatic fauna of this region.We exposed the larvae to sediments from Selama River (SR), Permatang Rawa River (PRR) and Kilang Ubi River (KUR) at various durations (0, 6, 12, 24 and 48 h). The larval mortality was monitored, whereas DNA damage in survivors’ cells was determined using the comet assay. Pollution level indexed by the amounts of heavy metals and other organic contaminants in the sediment showed progressive increases from SR to PRR to KUR. Highly polluted sediments (PRR to KUR) were detrimental to C. kiiensis larvae, most of which did not survive following exposure for long periods. DNA analyses revealed greater damages in nuclei derived from larvae maintained on polluted sediments, in particular, those from KUR. The effects on the genomic material of C. kiiensis larvae occurred in a timedependent manner, with damage level increasing as exposure time progressed. Our results highlight the genotoxic properties of polluted sediments.More importantly, this study showed that C. kiiensis larvae could respond to different levels of pollution with respect to exposure time. It is concluded that C. kiiensis larvae is a potential candidate for river ecotoxicological monitoring.